Efektivitas Komunikasi Organisasi Terhadap Koordinasi Pelayanan Ekspor Impor (Studi Kasus Antara PT IPC Petikemas Dan Shipping Agency Di Pelabuhan Panjang) - Fahrudin, Fatrick (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This study aims to examine the effectiveness of organizational communication on export-import service coordination at the Port, focusing on the interaction between PT IPC Petikemas and Shipping Agency. Effective communication is a key element in ensuring smooth operations and collaboration between various stakeholders at the port. This study uses a qualitative approach with a case study method to explore how established communication can affect the coordination and efficiency of export-import services. The results show that structured, transparent, and timely communication between PT IPC Petikemas and Shipping Agency plays an important role in accelerating operational processes, reducing errors, and improving service quality. Barriers in communication, such as miscommunication or delays in information, have been shown to hamper workflow and have a negative impact on overall service. These findings underscore the importance of strengthening organizational communication to support better coordination in export-import services at the port.